Clinical Insights Into Novel Immune Checkpoint Inhibitors - Lee, Jii Bum; Ha, Sang-Jun; Kim, Hye Ryun (Frontiers in Pharmacology, 2021)
The success of immune checkpoint inhibitors (ICIs), notably anti-cytotoxic T lymphocyte as-sociated antigen-4 (CTLA-4) as well as inhibitors of CTLA-4, programmed death 1 (PD-1), and programmed death ligand-1 (PD-L1), has revolutionized treatment options for solid tu-mors. However, the lack of response to treatment, in terms of de novo or acquired resistance, and immune related adverse events (IRAE) remain as hurdles. One mechanisms to overcome the limitations of ICIs is to target other immune checkpoints associated with tumor microen-vironment. Immune checkpoints such as lymphocyte activation gene-3 (LAG-3), T cell im-munoglobulin and ITIM domain (TIGIT), T cell immunoglobulin and mucin-domain contain-ing-3 (TIM-3), V-domain immunoglobulin suppressor of T cell activation (VISTA), B7 hom-olog 3 protein (B7-H3), inducible T cell costimulatory (ICOS), and B and T lymphocyte at-tenuator (BTLA) are feasible and promising options for treating solid tumors, and clinical tri-als are currently under active investigation. This review aims to summarize the clinical aspects of the immune checkpoints and introduce novel agents targeting these checkpoints.